2014
DOI: 10.1515/cclm-2013-0801
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s disease specific pancreatic antibodies: clinical and pathophysiological challenges

Abstract: Crohn's disease (CrD) and ulcerative colitis (UC) are the main inflammatory bowel diseases (IBD). IBDspecific humoral markers of autoimmunity in the form of autoantibodies have been reported first in the late 1950s by demonstrating the occurrence of autoimmunity in UC, while humoral autoimmunity in CrD can be traced back to the 1970s. Ever since, the pathophysiological role of autoimmune responses in IBDs has remained poorly understood. Notwithstanding, autoreactive responses play a major role in inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 103 publications
0
28
1
Order By: Relevance
“…However, analysis of GP2A-IgA levels within CrD subgroups with exclusive colon or ileum localized disease did not substantiate this suggestion. is is in contrast with previous ndings [8,17,18] and may be related to the relatively small group sizes in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, analysis of GP2A-IgA levels within CrD subgroups with exclusive colon or ileum localized disease did not substantiate this suggestion. is is in contrast with previous ndings [8,17,18] and may be related to the relatively small group sizes in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…These differences could be due to the different patient characteristics of the respective cohorts or different assay performance of the ELISA employed for autoantibody testing. Indeed, detection of autoantibodies to hnRNP seems to require the preservation of conformational epitopes which can be influenced by the recombinant expression system and coating procedure for ELISA-solid phases utilized as demonstrated for other autoantigenic targets as well [24, 25]. Furthermore, Russian patients with RA can demonstrate different prevalences of RA-specific autoantibodies than reported in studies with Caucasian patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…38 Thus, GP2 on M cells can act as a transcytotic receptor for bacterial antigens, and worthy of note, participate in the mucosal immune responses to these particular bacteria; a subset of commensal and pathogenic enterobacteria (E. coli and S. Typhmurium). 46,47 Other research has shown that a murine GP2 (mGP2)-specific aptamer, isolated using Systematic Evolution of Ligands by EXponential enrichment (SELEX), with a loop structure and the nucleotide sequence, AAAUA (both important for binding to mGP2), binds to mGP2 expressed on the cell surface, indicating that the aptamer serves as a promising tool for testing M-cell-targeted vaccine delivery in murine model systems. 48 …”
Section: Glycoprotein 2 (Gp2)mentioning
confidence: 99%